2015
DOI: 10.1186/s13717-015-0036-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land use/land cover changes on ecosystem services in the Nenjiang River Basin, Northeast China

Abstract: Introduction: The Nenjiang River Basin is an important foodstuff base and eco-environmental fragile area in Northeast China. With the rapid rise in human population, human-induced changes in land use/land cover form an important component of regional environment and ecosystem service change. At the local and regional level, the ecosystem service concept can act as a decision support tool for a stakeholder to reach sustainable land use management. However, the prevailing ecosystem service evaluation would produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 19 publications
2
36
3
Order By: Relevance
“…Therefore, future ESV estimation studies should use high resolution remote sensing data for improved accuracy in land use classification. Field investigation and interviews with local leaders, experts, and residents should also be integrated [54].…”
Section: Data Selectionmentioning
confidence: 99%
“…Therefore, future ESV estimation studies should use high resolution remote sensing data for improved accuracy in land use classification. Field investigation and interviews with local leaders, experts, and residents should also be integrated [54].…”
Section: Data Selectionmentioning
confidence: 99%
“…The loss of ESVs due to LULCC has not been investigated in this study. However, it has been shown that in Nenjiang River Basin, Northeast China, all of the ESVs declined from 1980 to 2005 [68]. The total decline of $2.43 billion was mainly due to the cultivation of grassland (14.34% of the area in 1980) and wetlands (4.62% of the area in 1980) in the downstream plain.…”
Section: Amount Of Carbon Stock Removed Due To Deforestationmentioning
confidence: 99%
“…For example, bias in some cases such as underestimated farmland ESV and overestimated wetland ESV [35]. Their derived ESV mirrored the economic level of developed countries (e.g., United States and European countries) instead of developing countries such as China [18,25,54]. For Chinese terrestrial ecosystem services Xie et al (2003) developed the equivalent per-unit-area following the same methodology proposed by Costanza et al (1997) [2].…”
mentioning
confidence: 99%